FUNGSI SOSIAL ZIARAH PADA MASYARAKAT JAWA: Analisis Tradisi Ziarah di Wonoyoso - Fikria Najitama (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbstractFor Javanese people, pilgrimage (ziarah) is an important part of the ritual of life. Wonoyoso, as part of the Java, also has a strong tradition of pilgrimage. For Wonoyoso people, pilgrimage is not only based on ‘tradition’, but also includes aspects of rational and emotional value. Thus, pilgrimage is a complex behavior that is not enough to be seen from one aspect only. This study attempted to look at social functions of pilgrimage in Wonoyoso. Thus, this study attempts to understand pilgrimage undertaken by Wonoyoso people by focusing on socio- anthropological aspects. This study results that in the pilgrimage in Wonoyoso have important elements that sustain them: the leader and groups. Moreover, it turns out has a function pilgrimage group integration. This fact can be seen from a system of norms that bind individuals. There are three groups integration: the integration of religious groups (santri), the integration of children of the family (bani), and the integration of family groups. It proves that the ritual pilgrimage in addition to having a very strong personal implications, but also has a social function. Thus, indirectly pilgrimage is ‘tradition’ to bind the individual in a social group.Kata Kunci: ziarah, tradisi, ritual, fungsi sosial, integrasi kelompok